Does Need for Cognition Moderate the Relationship Between Eyewitness Age and Perceived Credibility? - Pittman, Anna E (2012)
The relationship between age and perceived credibility was examined, particularly whether or not middle-aged witnesses were perceived as more credible than older eyewitnesses. Additionally, I was interested in whether or not the relationship between age and credibility was moderated by need for cognition. Participants read a trial transcript about a child pedestrian-car accident wherein a defendant was charged with manslaughter. The sole eyewitness, either a 49 or 79 year-old male, testified that the child hit his head on a rock upon stepping off the curb before being struck by the defendant’s vehicle. Transcripts included direct and cross-examination with half accompanied by the eyewitness’ photo. Participants rated witness credibility on nine dimensions including competence, honesty, and suggestibility, then rendered a verdict. Participants completed the Need for Cognition Scale and a questionnaire measuring attitudes towards punishment. There was a significant three-way interaction between age, information type, and need for cognition on perceived credibility ratings. Perceived credibility ratings were positively correlated with judgments of guilt. Results are discussed in terms of their implications within the criminal justice system